Fine needle aspiration cytology comparison of diagnosed thyroid nodules diagnosis with postoperative histopathology - Turan, Gülay; Kocaöz, Servet (International Surgery Journal, 2018)
Background: Around 2.5% of male cancer in Turkey, 12% of female cancers include cancers of the thyroid. Early diagnosis and correct treatment of thyroid cancers is therefore important. However, in addition to preventing the complications, patients not to be subjected to unnecessary thyroid procedure depend on the pre-detection of that whether the nodules are benign or malign. The objectives of the study were to investigate whether fine needle aspiration (FNA) cytology of thyroid nodules is sufficient for diagnosis. Thyroid FNA result is based on the standardized Bethesda System for Reporting Thyroid Cytopathology (TBSRTC). Methods: FNA cytology reports of 1808 patients for the period between January 2011 and December 2017 in Atatürk City Hospital, which is located in Balıkesir province, in the western part of Turkey, were retrospectively analyzed. Cytology results were reported as follows: non-diagnostic, benign, atypia (AUS) or follicular lesion (FLUS) of undetermined significance, follicular neoplasm or suspected follicular neoplasm (FN), suspected malignity and malign. They were compared with postoperative histopathology result. Results: According to the thyroid FNA cytology, 409 patients were operated on, and the obtained specimens were histopathologically analyzed. The histopathological malignity rates of patients were detected to be as follows: 0.0%, 2.0%, 3.0%, 12.1%, 31.3% and 51.5%. It was detected that malign thyroid cancer was detected to be seen more in women and the age group of 31-60. The sensitivity value of the research was detected to be 92%, which was a significantly high ratio. Positive and negative predictive values were detected to be 97% and 92%, respectively. Conclusions: Where FNA cytology result is insufficient, FNA procedure should be repeated. FNA must be repeated with USG for cases with suspected AUS, FLUS and follicular neoplasm.